Alternative of clinical end point selection for metronomic studies. Issue 3 (July 2017) - Kumar, Ramesh; Jose, Jesna; Vishwakarma, Gajendra K; Bhattacharjee, Atanu
Abstract : The dose of a therapeutic agent is decided by its tolerability. The metronomic chemotherapy is a repeated administration of the chemotherapeutic agents at the low dose. It is difficult to establish the best dose in metronomic chemotherapy through tolerance level. The clinical benefit of any treatment efficacy is demonstrated by overall survival; however, it takes longer duration follow-up. Defining the earlier end points is important as it is a parameter that helps determine the timing of occurrence the event of interest. The surrogate biomarker can be considered as a substitute for a clinical end point. A surrogate end point can provide earlier measurement in comparison to a traditional clinical end point. It also requires lesser follow-up time and hence small sample size. This paper explores the importance of surrogate marker to be considered for assessing the metronomic studies. It is concluded that the surrogate marker can be considered as an alternative of traditional clinical end points to assess the earlier outcome effect of metronomic chemotherapy.